2009
DOI: 10.1108/14725960910952505
|View full text |Cite
|
Sign up to set email alerts
|

Modelling structure of customer satisfaction with construction

Abstract: PurposeThe purpose of this paper is to build a tested model and framework for describing the structure and factors influencing customer satisfaction in the construction industry.Design/methodology/approachThe paper introduces a structural equation model illustrating the interdependencies of the factors influencing customer satisfaction. Data for the model are based on 831 assessments obtained from project customers with regard to the successfulness of the project.FindingsThe results show that customer satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 44 publications
1
48
0
1
Order By: Relevance
“…Several authors have emphasized the multi-dimensional nature of service quality and its influence on construction client satisfaction (Kang, James 2004;Yang, Peng 2008;Kärnä et al 2009;Li et al 2013;Aliakbarlou et al 2017;Hadidi et al 2017;Ihtiyar 2017). However, a review of the relevant literature suggests that the findings in other countries' context may not be applicable in Cambodia, which is obviously due to the difference in the perception of service quality among construction clients in the country.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several authors have emphasized the multi-dimensional nature of service quality and its influence on construction client satisfaction (Kang, James 2004;Yang, Peng 2008;Kärnä et al 2009;Li et al 2013;Aliakbarlou et al 2017;Hadidi et al 2017;Ihtiyar 2017). However, a review of the relevant literature suggests that the findings in other countries' context may not be applicable in Cambodia, which is obviously due to the difference in the perception of service quality among construction clients in the country.…”
Section: Discussionmentioning
confidence: 71%
“…What differentiates leading construction companies from others is service excellence, which improves productivity, maintains client loyalty, and creates positive word-of-mouth advertising, all of which can create advantages in the competitive business environment. Due to its significance, client satisfaction has received broad attention in the literature (Barret 2000;Torbica, Stroh 2001;Maloney 2002;Yasamis et al 2002;Yang, Peng 2008;Kärnä et al 2009;Li et al 2013;Hsu, Juan 2016;Aliakbarlou et al 2017;Hadidi et al 2017). For example, construction client satisfaction was perceived to be the most significant determinant of success in the Turkish construction industry context (Arslan, Kivrak 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches were used to classify the factors that lead to customer satisfaction in construction. For instance, Kärnä, et al [2] classified them as: quality assurance and handover, environmental and safety at work, personnel, cooperation and site supervision and subcontracting. Within this research, the identified drivers were classified into two categories.…”
Section: Development Of the Iics 1) Identification Validation And CLmentioning
confidence: 99%
“…Today's competitive environment entails that companies have to understand their customers' expectations and preferences and use them as a guide to improve their performance and achieve competitive advantage [1], [2], [3]. In dynamic business conditions, it is critically important to perceive and satisfy customer needs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many constructs in research cannot be expected to be independent of each other, so the oblique rotation approach would be appropriate to obtain several theoretically meaningful factors (Hair et al, 1998). Promax is one of the most commonly used oblique rotation methods (DeCoster, 1998;Biber, 2009) which has been adopted by a number of researchers (Pham and Swierczek, 2006;Lam et al, 2008;Chan and Lee, 2009;Kärnä et al, 2009). Therefore, Promax rotation method was finally applied to this study for further discussion.…”
Section: Factor Analysis Of Pfss Benefitsmentioning
confidence: 99%